MANAJEMEN WAKTU TERHADAP PELAKSANAAN PROYEK ASRAMA BALAI LATIHAN KERJA KOTA SAMARINDA - Habir Habir (Prodi Ilmu Administrasi Negara, 2020)
The use of appropriate time management, practical, fast and safe isvery helpful in completing work on a construction project. So that every setplan can be achieved. Own time management is the process of planning,compiling and controlling the schedule of project activities. . Factors neededin construction projects are man (man), building material (material),equipment (machine), implementation method (method), money (money),information (information) and time (time).In the construction project of the Training Hall Dormitory Building inSamarinda City, East Borneo which consists of 4 parts of the building, but inthe process of monitoring work refers to the 2016 S and Ms Curve asmaterial for monitoring development work evaluations, the conclusion is thatthe monitoring results using ms project are necessary planning time for theimplementation in the field later so that at the time of development there areno delays and timely development, quality, and quality.